Chasing the mythical ten percent: parental hearing status of Deaf and hard of hearing students in the United States - Mitchell, Ross E; Karchmer, Michael A (Sign Language Studies, 2004)
, This article investigates the basis for the frequently reported stat ement that ten percent of deaf persons are born to families with one o r more deaf parents. The prevalence of deaf children born to deaf pare nts (deaf-of-deaf) is important because it is often cited when describ ing linguistic and educational advantages, along with social and cultu ral differences, associated with deaf children born to deaf parents co mpared to deaf children of hearing parents. This analysis provides a c urrent estimate for the distribution of parental hearing status among deaf and hard of hearing students in United States using data from the Annual Survey of Deaf and Hard of Hearing Children and Youth (1999–20 00). This is the first national estimate that fully utilizes the disti nction between children having deaf parents and hard of hearing parent s, as well as hearing parents. The authors propose that the key demogr aphic to report, other than that the overwhelming majority of deaf and hard of hearing students have hearing parents, is whether the child h as one or two deaf parents. The annual survey findings indicate that l ess than five percent of deaf and hard of hearing students receiving s pecial education are known to have at least one deaf parent, which is less than half of the presumed ten percent. Reasons for the difference between the present and previous estimates are suggested.